Antipsychotics Use Is Associated With Greater Adherence to Cardiometabolic Medications in Patients With Schizophrenia: Results From a Nationwide, Within-subject Design Study. (21st July 2021) - Solmi, Marco; Tiihonen, Jari; Lähteenvuo, Markku; Tanskanen, Antti; Correll, Christoph U; Taipale, Heidi
Abstract: Background: People with schizophrenia/schizoaffective disorder (schizophrenia) die early, largely due to cardiovascular-related mortality. Antipsychotics are associated with lower mortality. We aimed to explore whether antipsychotic use can reduce discontinuation of medications for cardiovascular risk factors and diseases ("cardiometacolic drugs"), using a within-study design controlling for subject-related factors. Methods: Persons diagnosed with schizophrenia between 1972 and 2014, aged <65 years at cohort entry were identified in Finnish national databases. Four subcohorts were formed based on cardiometabolic drug use during the follow-up period, 1996–2017, namely statin ( n = 14, 047), antidiabetic ( n = 13, 070), antihypertensive ( n = 17, 227), and beta-blocker ( n = 21, 464) users. To control for subject-related factors, including likelihood of adherence as a trait characteristic, we conducted a within-subject study comparing the risk of discontinuation of each cardiometabolic drug during periods on vs off antipsychotics within each subject. We also accounted for number of psychiatric and nonpsychiatric visits in sensitivity analyses. Results: In 52, 607 subjects with schizophrenia, any antipsychotic use vs nonuse was associated with decreased discontinuation risk of antidiabetics (adjusted hazard ratio [aHR] = 0.56, 95% confidence interval [CI] = 0.47–0.66), statins (aHR = 0.61, 95%CI = 0.53–0.70), antihypertensives (aHR = 0.63, 95%CI = 0.56–0.71), and beta-blockers (aHR = 0.79, 95%CI = 0.73–0.87). Antipsychotics ranking best for discontinuation of all cardiometabolic drug categories were clozapine (aHR range = 0.34–0.55), followed by olanzapine (aHR = 0.43–0.71). For statins, aHRs ranged from aHR = 0.30 (95%CI = 0.09–0.98) (flupentixol-long-acting injectable (LAI) to aHR = 0.71 (95%CI = 0.52–0.97) (risperidone-LAI), for anti-diabetic medications from aHR = 0.37 (95%CI = 0.28–0.50) (clozapine) to aHR = 0.70 (95%CI = 0.53–0.92) (quetiapine), for antihypertensives from aHR = 0.14 (95%CI = 0.04–0.46) (paliperidone-LAI) to aHR = 0.69 (95%CI = 0.54–0.88) (perphenazine), for beta-blockers from aHR = 0.55 (95%CI = 0.48–0.63) (clozapine) to aHR = 0.76 (95%CI = 0.59–0.99) (perphenazine-LAI). The decreased risk of discontinuation associated with antipsychotic use somewhat varied between age strata. Sensitivity analyses confirmed main findings. Discussion: In this national database within-subject design study, current antipsychotic use was associated with substantially decreased risk of discontinuation of statins, anti-diabetics, antihypertensives, and beta-blockers, which might explain reduced cardiovascular mortality observed with antipsychotics in people with schizophrenia.